ANALISIS VARIASI MEDIA PENDINGIN KONDENSOR TERHADAP RASIO PELEPASAN KALOR DAN COEFISIEN OF PERFORMANCE (COP) PADA MESIN PENDINGIN - Digdo Listyadi Setyawan; Eko Widodo; Hasby R (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
Household refrigerating machine (refrigerator) is a household appliance that is widely used in the family in Indonesia. The condenser is one of the essential components of the refrigerator that functions as a heat exchanger which is composed of the equivalent gas-phase refrigerant into a liquid. A crucial element of the condenser to cool the evaporator with the faster is the rate of heat release, coefisien of performance (COP). This research was conducted by varying the experimental cooling medium in the condenser of household refrigerating machine (refrigerator), such as the natural air cooling medium, the addition of fins and additional fan area 14,4 Watt. It aims to improve the coefficient of achievement refrigeration, heat release ratio and cooling rate speed. The results showed a coolant condenser with fan 14.4 W produces the highest COP value, 4,73, and the ratio of the smallest heat release ratio, 1,2. The larger the COP and the smaller pelepasn calorific value, indicating that the machine work better. Keywords : media pendingin kondensor, rasio pelepasan kalor, COP, mesin pendingin